Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Let's simplify the given expression step-by-step.
Given:
[tex]\[ \frac{\left(4 p^{-4} q\right)^{-2}}{10 p q^{-3}} \][/tex]
First, simplify the numerator \(\left(4 p^{-4} q\right)^{-2}\):
1. Distribute the exponent \(-2\):
[tex]\[ \left(4 p^{-4} q\right)^{-2} = 4^{-2} \cdot (p^{-4})^{-2} \cdot (q)^{-2} \][/tex]
2. Simplify each term:
[tex]\[ 4^{-2} = \frac{1}{4^2} = \frac{1}{16} \][/tex]
[tex]\[ (p^{-4})^{-2} = p^{8} \][/tex]
[tex]\[ q^{-2} = q^{-2} \][/tex]
Thus, we have:
[tex]\[ \left(4 p^{-4} q\right)^{-2} = \frac{1}{16} \cdot p^8 \cdot q^{-2} = \frac{p^8}{16 q^2} \][/tex]
Next, revisit the entire expression with the updated numerator:
[tex]\[ \frac{\frac{p^8}{16 q^2}}{10 p q^{-3}} \][/tex]
Simplify the denominator:
[tex]\[ 10 p q^{-3} = 10 p \cdot \frac{1}{q^3}= \frac{10 p}{q^3} \][/tex]
Therefore, the expression becomes:
[tex]\[ \frac{\frac{p^8}{16 q^2}}{\frac{10 p}{q^3}} \][/tex]
Use the property of division (divide by a fraction by multiplying by its reciprocal):
[tex]\[ \frac{p^8}{16 q^2} \cdot \frac{q^3}{10 p} = \frac{p^8 q^3}{16 q^2 \cdot 10 p} \][/tex]
Simplify by cancelling common factors:
[tex]\[ \frac{p^8 q^3}{160 p q^2} = \frac{p^{8-1} q^{3-2}}{160} = \frac{p^7 q}{160} \][/tex]
Thus, the equivalent expression to the given one is:
[tex]\[ \boxed{\frac{p^7 q}{160}} \][/tex]
So the correct answer among the provided options is:
[tex]\[ \frac{p^7 q}{160} \][/tex]
Given:
[tex]\[ \frac{\left(4 p^{-4} q\right)^{-2}}{10 p q^{-3}} \][/tex]
First, simplify the numerator \(\left(4 p^{-4} q\right)^{-2}\):
1. Distribute the exponent \(-2\):
[tex]\[ \left(4 p^{-4} q\right)^{-2} = 4^{-2} \cdot (p^{-4})^{-2} \cdot (q)^{-2} \][/tex]
2. Simplify each term:
[tex]\[ 4^{-2} = \frac{1}{4^2} = \frac{1}{16} \][/tex]
[tex]\[ (p^{-4})^{-2} = p^{8} \][/tex]
[tex]\[ q^{-2} = q^{-2} \][/tex]
Thus, we have:
[tex]\[ \left(4 p^{-4} q\right)^{-2} = \frac{1}{16} \cdot p^8 \cdot q^{-2} = \frac{p^8}{16 q^2} \][/tex]
Next, revisit the entire expression with the updated numerator:
[tex]\[ \frac{\frac{p^8}{16 q^2}}{10 p q^{-3}} \][/tex]
Simplify the denominator:
[tex]\[ 10 p q^{-3} = 10 p \cdot \frac{1}{q^3}= \frac{10 p}{q^3} \][/tex]
Therefore, the expression becomes:
[tex]\[ \frac{\frac{p^8}{16 q^2}}{\frac{10 p}{q^3}} \][/tex]
Use the property of division (divide by a fraction by multiplying by its reciprocal):
[tex]\[ \frac{p^8}{16 q^2} \cdot \frac{q^3}{10 p} = \frac{p^8 q^3}{16 q^2 \cdot 10 p} \][/tex]
Simplify by cancelling common factors:
[tex]\[ \frac{p^8 q^3}{160 p q^2} = \frac{p^{8-1} q^{3-2}}{160} = \frac{p^7 q}{160} \][/tex]
Thus, the equivalent expression to the given one is:
[tex]\[ \boxed{\frac{p^7 q}{160}} \][/tex]
So the correct answer among the provided options is:
[tex]\[ \frac{p^7 q}{160} \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.